A Bayesian Efficiency Analysis of Angolan Banks. (26th April 2016) - Barros, Carlos Pestana; Leão, Emanuel Reis; Macanda, Nkanga Pedro João; Mendes, Zorro
Abstract: This article studied the technical efficiency of Angolan banks from 2005 to 2012 using a Bayesian stochastic frontier model. The intermediation approach to banking was adopted. The results revealed that Angolan banks were very efficient and that efficiency varies little among the banks analysed. Furthermore, the differences in efficiency between foreign banks, public banks, large‐sized banks and banks that belong to a local conglomerate were examined. It was concluded that the greatest efficiency was to be found in the case of foreign banks. Since size and conglomerate membership do not seem to lead to greater bank efficiency, it was proposed that Angolan policymakers should promote competition in the banking sector.